WOMEN IN THE QUR’AN AND THEIR ROLE IN TEACHING THE ARABIC LANGUAGE AND CULTURE TO FORM AN ISLAMIC PERSONALITY - Chamidah, Dewi (Proceeding of International Conference on Islamic Education (ICIED); Vol 2 No 1 (2017): Proceeding of International Conference on Islamic Education (ICIED), 2017)
Women are half of society. Their existence must be recognized. We see from the wise those who attribute credit to the help of women, and said, "Behind every great woman." On the other side, we see philosophers who carry the female behind what happens in the world of fascination and crimes, even when it is said that when a disaster occurs or the crime of "looking for women".The teaching of Arabic as a foreign language requires planning and organizing as best as possible so that it can be taught and to achieve its desired goals, so that we do not do trivial work for no purpose or purpose. On this basis, education needs a good and appropriate approach. Women were distinguished through ancient and modern times by their active participation in various fields, playing the role of poet, queen, artist, warrior and artist. Women continue to be tired and tired in order to build the family and take care of the house. As a mother, it is the responsibility of the generations to grow up and take responsibility for managing the house and its economy, which makes the tasks that women exercise in our societies can not be underestimated or underestimated. It helps them to use them in mutual understanding so that they can find a joint response that enables them to resist the intellectual sabotage practiced by the malicious parties to distort the true teachings of Islam and to break that bond that connects the sons of  the Islamic nation with an intellectual and spiritual bond.